A purge and trap technique to capture volatile compounds combined with comprehensive two‐dimensional gas chromatography/time‐of‐flight mass spectrometry to investigate the effect of sulfur‐fumigation on Radix Angelicae Dahuricae. (12th March 2014) - Cao, Gang; Li, Qinglin; Zhang, Jida; Cai, Hao; Cai, Baochang
ABSTRACT Sulfur‐fumigation is known to reduce volatile compounds that are the main active components in herbs used in herbal medicine. We investigated changes in chemical composition between sun‐dried and sulfur‐fumigated Radix Angelicae Dahuricae using a purge and trap technique to capture volatile compounds, and two‐dimensional gas chromatography/time‐of‐flight mass spectrometry for identification. Using sun‐dried Radix Angelicae Dahuricae samples as a reference, the results showed that 73 volatile compounds, including 12 sulfide compounds, were found to be present only in sulfur‐fumigated samples. Furthermore, 32 volatile compounds that were found in sun‐dried Radix Angelicae Dahuricae samples disappeared after sulfur‐fumigation. The proposed method can be applied to accurately discriminate sulfur‐fumigated Radix Angelicae Dahuricae from different commercial sources. Copyright © 2014 John Wiley & Sons, Ltd.